2021
DOI: 10.1021/acschemneuro.0c00655
|View full text |Cite
|
Sign up to set email alerts
|

((E)-N-(4-(((2-Amino-5-phenylpyridin-3-yl)imino)methyl)pyridin-2-yl)cyclopropanecarboxamide) Ameliorated Aβ1–42-Induced Alzheimer’s Disease in SD Rats by Inhibiting Oxidative Stress and Apoptosis

Abstract: Our study investigated the protective effects of ((E)-N-(4-(((2-amino-5-phenylpyridin-3-yl)imino)methyl)pyridin-2-yl)cyclopropanecarboxamide) 9b, a novel glycogen synthase kinase-3β (GSK-3β) inhibitor, on the learning and memory function of rats with amyloid-β 1−42 (Aβ 1−42 )-induced Alzheimer's disease (AD) and explored the possible mechanisms. Sixty male Sprague-Dawley (SD) rats were randomly divided into five groups: the control, Aβ, donepezil, and low-dose and highdose 9b groups. The rats in the Aβ, donepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…These changes suggested the involvement of apoptosis under the double effect of Abeta and glutamate load. Parallel results also demonstrated that Abeta 1–42 [ 36 38 ] and glutamate [ 38 42 ] induced apoptosis in neuronal SH-SY5H cells and primary cultured neurons, which manifested as increased BAX/BCL2 ratio and expression of CCP3. Together, these findings showed that neuronal apoptosis and necrosis were involved in the process under the double effects of Abeta and glutamate load.…”
Section: Discussionmentioning
confidence: 70%
“…These changes suggested the involvement of apoptosis under the double effect of Abeta and glutamate load. Parallel results also demonstrated that Abeta 1–42 [ 36 38 ] and glutamate [ 38 42 ] induced apoptosis in neuronal SH-SY5H cells and primary cultured neurons, which manifested as increased BAX/BCL2 ratio and expression of CCP3. Together, these findings showed that neuronal apoptosis and necrosis were involved in the process under the double effects of Abeta and glutamate load.…”
Section: Discussionmentioning
confidence: 70%
“…These changes suggested the involvement of apoptosis under the double effect of Abeta and glutamate load. Parallel results also demonstrated that Abeta1-42 [35][36][37] and glutamate [37][38][39][40][41] induced apoptosis in neuronal SH-SY5H cells and primary cultured neurons, which manifested as increased BAX/BCL2 ratio and expression of cleaved caspase 3. Together, these ndings suggested the involvement of neuronal necrosis and apoptosis under the double effects of Abeta and glutamate load.…”
Section: Discussionmentioning
confidence: 75%